Struktur Komunitas dan Sebaran Bulu Babi (Echinoidea) di Kawasan Padang Lamun Pantai Serangan, Bali - Panji Agung Purnomo, I Gede; Sila Dharma, I Gusti; Putra, I Nyoman Giri (Journal of Marine Research and Technology, 2019)
Sea urchin is one of the biota that inhabiting coral reef and seagrass ecosystems. This spesies is commontly found in hard substrate, especially the substrate in seagrass beds which is a mixture of sand and coral fragments (Aziz, 1994). Sea urchins can be used as indicator organisms for water quality because sea urchins will become one of the first organisms to show signs of pressure (Yulianto, 2010). Serangan Island, geographically located in South Denpasar Subdistrict, Denpasar City, Bali Province which has a sediment in the form of coarse white sand mixed with coral fragments with high water activity. Based on the results of a study on the eastern coast of Serangan, sea urchins consisting of 5 species : D. setosum, E. diadema, E. calamaris, E. mattei, D. palmeri with dominanance species found is D. setosum sea urchins. Densities of sea urchins found in all stations was dominated by D. setosum with a total value sea urchin of 4.3 ind / m2 while the lowest density was in sea urchins of E. calamaris and E. diadema with a total value of 2.5 ind / m2 . Distribution pattern of sea urchins in Pantai Serangan, has a uniform distribution pattern (v < m) and clumped (v > m). D. setosum and E. matthei have uniform distribution with values of 0.29 and 0.21 while E. diadema, E. calamaris and D. palmeri have clustered distribution.